Food Security Based on Livelihood Assets: The Dominant Role of Financial Capital in Rural Areas for Sustainable Development - Risma Nurmilah; Ismet Ismetullah; Evi Martaseli; Venita Sofiani; Dine Meigawati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Food security issues have become a top priority in the Sustainable Development Goals (SDGs), particularly in efforts to meet basic human needs. The concept of food security is no longer limited to availability, but also encompasses access, which is influenced by livelihood assets. This study aims to analyze household food security in supporting SDG 2 based on the Sustainable Livelihood Approach in rural areas. A mixed-methods approach was employed, with a quantitative dominance through surveys of 100 households, analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that financial capital has a significant effect on food security and serves as a full mediator in the relationship between livelihood assets and food security. Human, social, physical, and natural capital do not have a direct significant effect, but exert indirect influence through financial capital. These results support the entitlement theory, which states that economic capacity determines access to food. Therefore, household food security in rural areas is more strongly determined by economic capacity than by resource availability, making access the dominant factor in achieving food security.